SOSIALISASI LITERASI DIGITAL BAGI MASYARAKAT KECAMATAN ALAM BARAJO KOTA JAMBI JELANG PEMILU 2024 - Cholillah Suci Pratiwi; Usman Usman; Wahyu Rohayati (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
The development of technology which affects all lines of people's lives means that people have to adapt to these technological developments. In this phenomenon, people are able to utilize technology, such as gadgets, laptops and other technology as tools to help with daily activities. With gadgets, the process of exchanging and disseminating information becomes easier. One of the impacts is a large and massive flood of information, making it difficult for people to digest and verify the various news they receive. The method for implementing this community service activity consisted of observation, design and socialization of digital literacy, as well as monitoring and evaluation. Through this activity, it is hoped that the people of Alam Barajo District would have a better understanding of digital literacy. The results of digital literacy outreach showed an increase in public understanding of the concept of digital literacy. This can be seen from a significant increase in public knowledge of the importance of digital literacy in facing the dynamics of information in the digital era. Socialization of digital literacy for the community has had a significant positive impact. Increasing public understanding of digital literacy and changes in behavior in using social media show the success of the implementation methods that have been implemented. A positive response to outreach materials also shows an approach that is relevant to the local needs of the community and increases the effectiveness of message delivery.